2016
DOI: 10.20944/preprints201608.0093.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental Health in Cypriot Citizens of the Rural Health Centre Kofinou

Abstract: Abstract:Objective: The main purpose of this study was to investigate the mental health of Cypriot citizens living in the current difficult period of economic recession. The specific objective was to investigate the different factors (gender, age, socio-economic factors, etc.) that may affect the levels of emotional distress, anxiety, and depression in patients attending the Rural Health Centre of Kofinou. Materials and Methods: The sample consisted of a total of 300 Cypriots who visited Kofinou Health Centre … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…According to our research, several studies in different countries agree that during the economic crisis the prevalence of major depressive episodes and major depressive syndromes increased in the general population in the years following the Great Recession of 2008. More specifically, evidence from Greece (Economou, Madianos, Peppou, Patelakis, & Stefanis, 2013; Madianos et al, 2011) Spain (Gili et al, 2012; Sicras-Mainar & Navarro-Artieda, 2016), Italy (Mucci et al, 2016), Cyprus (Stavrou et al, 2016), and the Republic of China (Lee et al, 2010) suggest what is mentioned above. Apart from that, unemployed, unskilled workers, bankrupt citizens and people who lost their previous social status during the recession seem to be more vulnerable in terms of psychological health, chronic stress and psychological distress (Zissi & Stalidis, 2017).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…According to our research, several studies in different countries agree that during the economic crisis the prevalence of major depressive episodes and major depressive syndromes increased in the general population in the years following the Great Recession of 2008. More specifically, evidence from Greece (Economou, Madianos, Peppou, Patelakis, & Stefanis, 2013; Madianos et al, 2011) Spain (Gili et al, 2012; Sicras-Mainar & Navarro-Artieda, 2016), Italy (Mucci et al, 2016), Cyprus (Stavrou et al, 2016), and the Republic of China (Lee et al, 2010) suggest what is mentioned above. Apart from that, unemployed, unskilled workers, bankrupt citizens and people who lost their previous social status during the recession seem to be more vulnerable in terms of psychological health, chronic stress and psychological distress (Zissi & Stalidis, 2017).…”
Section: Resultsmentioning
confidence: 83%
“…According to this review it seems that economic downturn and its outcomes can effect negatively the psychological state either of the population as a whole or of specific subgroups. Some studies focused on mental health problems in general (Buffel et al, 2015a; Chen et al, 2012; Córdoba-Doña et al, 2016; Drydakis, 2015; Odone et al, 2017; Starace et al, 2017; Tamayofonseca et al, 2018; Utzet et al, 2016) while others focused on more specific issues such as depression, anxiety and stress (Economou, Madianos, Peppou, Patelakis, & Stefanis, 2013; Gili et al, 2012; Lee et al, 2010; Madianos et al, 2011; Mucci et al, 2016; Sicras-Mainar & Navarro-Artieda, 2016; Stavrou et al, 2016; Zissi & Stalidis, 2017). All of those studies agree that in some way there is a positive correlation regarding the financial crisis and mental health issues which means that the deeper the economic crisis, the grater is the effect on population’s mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Also, almost the entire sample suffered from a chronic disease with predominant hypertension, hypercholesterolemia and coronary disease. The association of depression with the presence of chronic diseases has occupied the literature extensively (47)(48)(49). However, the percentage of depressive symptoms was significantly higher among participants who had osteoporosis and to those who suffered from multiple chronic illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in Cyprus exploring the impact of the financial crisis on the mental health of Cypriots showed that this was a major predisposing factor in the development of anxiety and depressive symptoms in the participants ( 8 ).…”
Section: Economymentioning
confidence: 99%